Effects of environmental factors on anaerobic granular sludge in upflow anaerobic sludge blanket reactors - 453381 Shen, Chun Fang (London, Ont. : Univ of Western Ontario, 1993)
Thesis (PhD) - University of Western Ontario, 1993